2022
DOI: 10.1038/s41467-022-33217-9
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating syngas-to-aromatic conversion via spontaneously monodispersed Fe in ZnCr2O4 spinel

Abstract: Spontaneous monodispersion of reducible active species (e.g., Fe, Co) and their stabilization in reductive atmospheres remain a key challenge in catalytic syngas chemistry. In this study, we present a series of catalysts including spontaneously monodispersed and enriched Fe on ZnCr2O4. Deep investigation shows remarkable performance in the syngas-to-aromatic reaction only when monodispersed Fe coupled with a H-ZSM-5 zeolite. Monodispersed Fe increases the turnover frequency from 0.14 to 0.48 s−1 without sacrif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…These findings suggested that the d-band electrons of metals could be tuned while preserving the catalyst structure, resulting in effective regulation of reaction activity primarily controlled by the metal oxide side. A similar approach was adopted by Wei et al , 25 introducing appropriate amounts of F–T metals, such as Fe and Co, into spinel-type ZnCr 2 O 4 to significantly improve CO conversion without sacrificing total aromatic selectivity, as depicted in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggested that the d-band electrons of metals could be tuned while preserving the catalyst structure, resulting in effective regulation of reaction activity primarily controlled by the metal oxide side. A similar approach was adopted by Wei et al , 25 introducing appropriate amounts of F–T metals, such as Fe and Co, into spinel-type ZnCr 2 O 4 to significantly improve CO conversion without sacrificing total aromatic selectivity, as depicted in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 99%
“…30 Monodispersed Fe species were obtained over ZnCr 2 O 4 spinel that restricted the formation of Fe x C y during syngas-to-aromatic reactions. 31 In this work, the sheet-like MgAl 2 O 4 spinel loaded with atomically dispersed Fe 3+ species was prepared via a simple impregnation method. However, these monodispersed Fe species were easy to migrate and agglomerate under the high reaction temperature (650 °C).…”
Section: T H Imentioning
confidence: 99%
“…Given that 100% isolated Fe 3+ species in Fe/3Mg7Al were demonstrated in the 57 Fe Mossbauer spectra, and the comparison of the imaginary part of FT-EXAFS spectra (Figure S6), this signal is likely attributed to the Fe−Al scattering in Fe/3Mg7Al. 31,38 In addition, the wavelet transform (WT) EXAFS contour plots of Fe 2 O 3 is exhibited in Figure 2c, the signals at ca. 3.8 and 6.1 Å −1 are assigned to Fe−O and Fe−Fe path, respectively.…”
Section: Effect Of Support Type On the Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…11–13 Aromatics, as some of the most important basic chemicals, are widely used for the production of polymers, plastics, paints, packaging, and films. 14–17 With the rapid shortage of fossil resources, the conventional production of aromatics from petroleum cracking cannot meet the rapidly increasing market demand. Thus, the production of aromatics with high yields via the non-fossil route of CO 2 hydrogenation using renewable hydrogen sources is significantly attractive for mitigating the CO 2 emissions and realizing carbon neutrality.…”
Section: Introductionmentioning
confidence: 99%